2020
DOI: 10.29322/ijsrp.10.09.2020.p105102
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Self-reported Symptoms of Cabin Fever among Quezon City University Students during the Covid19 Pandemic

Abstract: The Covid-19 pandemic has changed our way of life and the education sector is one of the most affected by this global crisis. This study primarily aims to determine the effects of the implementation of the Community Quarantine in Metro Manila to the students of Quezon City University, particularly the manifestation of cabin fever. A total of 252 students participated in this study via online survey. The results show that majority of the respondents experience a none to mild symptoms of cabin fever. No gender d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 6 publications
0
7
0
12
Order By: Relevance
“…Several studies showed that the COVID-19 outbreak and its associated quarantine would be related to anxiety, depression, disturbed sleep, and post-traumatic stress disorder (Liang et al, 2020;Rajkumar, 2020). Estacio et al (2020) validated the impacts of the implementation of community isolation on cabin fever syndrome. They found that majority of the participants experience manifestations of cabin fever.…”
Section: Theoretical Background and Hypotheses Development Theoretica...mentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies showed that the COVID-19 outbreak and its associated quarantine would be related to anxiety, depression, disturbed sleep, and post-traumatic stress disorder (Liang et al, 2020;Rajkumar, 2020). Estacio et al (2020) validated the impacts of the implementation of community isolation on cabin fever syndrome. They found that majority of the participants experience manifestations of cabin fever.…”
Section: Theoretical Background and Hypotheses Development Theoretica...mentioning
confidence: 93%
“…Second, social distancing/lockdown limits citizens' outside activities and increases isolation time (Van Orden et al, 2021). It causes cabin fever syndrome (Estacio et al, 2020). Cabin fever refers to mental discomfort experienced in confined spaces for a long period (Crawford and Crawford, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Estacio, Lumibao, Reyes, & Avila (2020) menyebutkan bahwa psikolog, praktisi medis dan ahli kesehatan lainnya berpendapat bahwa, isolasi yang diakibatkan oleh fenomena alam seperti pandemi dapat menyebabkan kondisi yang disebut dengan cabin fever (Hartwell-Walker, 2020). Selain itu, Fritscher (2020) menekankan bahwa cabin fever merupakan respon yang umum terjadi ketika seseorang terisolasi atau terkurung dalam jangka waktu yang lama.…”
Section: Pendahuluanunclassified
“…Hal ini sesuai dengan teori-teori berikut, yang menjadi dasar untuk penelitian ini, cabin fever disebabkan oleh isolasi fisik karena fenomena alam seperti pandemi. Psikolog, praktisi medis, dan ahli kesehatan lainnya menyebutkan bahwa isolasi yang disebabkan oleh fenomena alam seperti pandemi dapat menyebabkan munculnya kondisi cabin fever (Estacio, Lumibao, Reyes, & Avila, 2020). Orang di seluruh dunia dapat mengalami kondisi cabin fever karena isolasi fisik, bahkan dapat dikatakan cabin fever adalah epidemi kedua di tengah pandemi COVID-19 (Porpora, 2020).…”
Section: Pembahasanunclassified
See 1 more Smart Citation